The relationship between visitor satisfaction, expectation andspending in a sport event - Reza Mortazavi (European Research on Management and Business Economics (ERMBE), 2021)
There are many studies on the determinants of visitor spending at sport events. However, few studiesinvestigate the effect of satisfaction on spending and even fewer relate this to visitor expectations. Thepresent study examines the case of the World Ski Championships 2015 which were held in Falun, Swe-den. A particular focus of the study is if and how visitor satisfaction influences visitors' expenditures.It is hypothesized and argued that spending depends on satisfaction relative to prior expectations. It isempirically found that those visitors with satisfaction greater than their expectations prior to the visitspend significantly more. A limitation of this study, however, is that the satisfaction is not measuredsystematically taking into consideration several dimensions of satisfaction which should be addressedin the future research.
Keywords: L83; Z20; Z30; 650; Visitor expenditures; Visitor satisfaction; Visitor expectation; Sport event; Sportveranstaltung; Urlaubsverhalten; Kundenzufriedenheit; Ausgaben; Schweden